Produk Unggulan Sebagai Daya Saing Daerah Studi Pengembangan UKM Di Kabupaten Brebes - Anis, Ashwar; Wibowo, Raden Arief (JIFA (Journal of Islamic Finance and Accounting), 2018)
The purpose of this study is to improve competitiveness in Brebes Dis- trict. This research uses qualitative research with common keywords. The study was conducted in Brebes District, covering the targeted area of the OVOP program as a manifestation of superior product development, and the Ministry of Industry and Commerce Department of Cooperatives and SMEs as the main data centers. Data analysis using descriptive qualitative by using description based on data available on research object. The results showed that excellent products in Brebes District as an effort to improve the competitiveness of regions have not achieved optimal results. From several excellent products avail- able in Brebes District, only two products are included in the main target, that is implementation of salted eggs and seaweed, while other production centers are still in development stage. However, the activ- ities undertaken show considerable prospective improvements, includ- ing increased production volumes and new product variations as a result of fostering and developing creativity and entrepreneurial in- novation. As a supporting factor, including the Brebes District Gov- ernment which has a strong commitment to implement the OVOP program on an ongoing basis, which is a superior resource that can be used as a flagship. Sources of funds, human resources and infrastruc- ture needs, especially for groups that can be used as capital to conduct OVOP activities as a whole. Stages of activities have been carried out appropriately and in accordance with their respective rules, al- though there are indications of overlap in coaching as there are no clear boundaries in defining individual business categories, and in- dustry groups. Keywords: Local original revenue, general allocation fund, special allocation fund, profit-sharing fund, human development index JEL Classification: E23, E26,l26